2018
DOI: 10.4186/ej.2018.22.5.87
|View full text |Cite
|
Sign up to set email alerts
|

Using Waste Vermiculite and Dolomite as Eco-Friendly Additives for Improving the Performance of Porous Concrete

Abstract: The present study investigated the applicability of waste vermiculite and dolomite as fine aggregate, known as appropriate mineral adsorbents to enhance the quality of urban runoff, for improving the mechanical properties of porous concrete. 180 samples were mixed by adding 5-30% vermiculite and dolomite, as fine aggregate, and combining them with ordinary sand; lime sand (combining of 5-15% of each). Results showed that although adding dolomite culminated in a minor reduction of permeability-average of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Dolomitic rock has high surfaced hardness as well as density, it also has low water demand which is of benefit since Pervious Concrete has limited water. [14,15] studies indicated improvement in compressive strength due to the dolomitic rock's high resistance to abrasion and to attrition another study indicated using Pervious Concrete with dolomitic rock as coarse aggregates resulted in improved durability and long-term performance in comparison to with other types of aggregates and it requires less energy to produce compared to other types of aggregates. Gauteng Province has 25% of its land covered in dolomitic rock [16], with upgrading, extensions and new infrastructure on the rise and this type of aggregates being locally discarded material due the risk related to foundation problems and groundwater, makes dolomitic rock very affordable.…”
Section: Dolomitic Rockmentioning
confidence: 99%
See 1 more Smart Citation
“…Dolomitic rock has high surfaced hardness as well as density, it also has low water demand which is of benefit since Pervious Concrete has limited water. [14,15] studies indicated improvement in compressive strength due to the dolomitic rock's high resistance to abrasion and to attrition another study indicated using Pervious Concrete with dolomitic rock as coarse aggregates resulted in improved durability and long-term performance in comparison to with other types of aggregates and it requires less energy to produce compared to other types of aggregates. Gauteng Province has 25% of its land covered in dolomitic rock [16], with upgrading, extensions and new infrastructure on the rise and this type of aggregates being locally discarded material due the risk related to foundation problems and groundwater, makes dolomitic rock very affordable.…”
Section: Dolomitic Rockmentioning
confidence: 99%
“…To determine the impact of compaction, samples were cast with and without compaction on the 3 sets of coarse aggregate sizes (7.1mm, 9.5mm and 19mm) dolomite rock. Different energies were administered in 3 layers (15,20,25) blows. Compacting Pervious Concrete is discouraged however there have been studies that found improved strength with minimum compaction.…”
Section: D) Concrete Casting and Curingmentioning
confidence: 99%
“…(1) e evaluation indexes include effective porosity, compressive strength, and general purification effect. e optimal value of each evaluation index is selected as the reference sequence (Y 0 ), as shown in equation (5). e results are shown in Table 7:…”
Section: Gray Correlation Analysismentioning
confidence: 99%
“…Permeable concrete has many applications, such as a base for terraces and greenhouses on pavements, as well as reducing flow during floods and improving flow in road drainage. In addition, it is helpful for the recharge of groundwater resources [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%